1988
DOI: 10.1029/jb093ib11p12969
|View full text |Cite
|
Sign up to set email alerts
|

Lithostratigraphy of the State 2–14 Borehole: Salton Sea Scientific Drilling Project

Abstract: Sedimentary rocks from the (California) State 2–14 research borehole of the Salton Sea Scientific Drilling Project, located in the Imperial Valley of southern California, were deposited in the continental basin of the Salton Trough. Lacustrine shale and siltstone are the dominant lithologies. Sandstones were deposited in lake margin, meander channel fill, and lacustrine delta environments. Framework modal clast compositions of the sandstones indicate a dominant Colorado River provenance. Rare pebbly mudstones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…A 10-12-km-deep basin fi lled since 5.3 Ma would require an average sediment accumulation rate of 1.9-2.3 km/m.y. (1.9-2.3 mm/yr), consistent with measured rates of 2-3 mm/yr in Pleistocene and Holocene deposits (Van Andel, 1964;Herzig et al, 1988).…”
Section: Plate Boundary Sedimentary Basinssupporting
confidence: 80%
See 1 more Smart Citation
“…A 10-12-km-deep basin fi lled since 5.3 Ma would require an average sediment accumulation rate of 1.9-2.3 km/m.y. (1.9-2.3 mm/yr), consistent with measured rates of 2-3 mm/yr in Pleistocene and Holocene deposits (Van Andel, 1964;Herzig et al, 1988).…”
Section: Plate Boundary Sedimentary Basinssupporting
confidence: 80%
“…Subsidence continued beneath the axial Salton Trough and produced a sedimentary basin as deep as 10-12 km, where Colorado River sediment is intruded by young mafi c and silicic sills (Elders et al, 1972;Fuis et al, 1984;Schmitt and Vazquez, 2006). Sediment accumulation rates of 2.2-2.3 mm/yr are indicated by presence of the 760 ka Bishop Tuff 1.7 km below the surface (Herzig et al, 1988).…”
Section: Plate Boundary Sedimentary Basinsmentioning
confidence: 98%
“…10). If the accumulation rate is similar to that documented nearby in rapidly subsiding depocenters of the Salton Trough (1-2 mm/yr; Herzig et al, 1988;Schmitt and Hulen, 2008;Dorsey et al, 2011;McNabb, 2013), we would predict a depth of ~1.2-2.4 km to the contact between predetachment and postdetachment deposits in the subsurface. Combining the asymmetric morphology of the Santa Rosa Mountains, wedge-shaped basin geometry beneath the southern Coachella Valley, and possible range of depth to the base of postdetachment deposits (Fig.…”
Section: Summary Of Observationsmentioning
confidence: 53%
“…The WSDF is a regional structure bounding a large supra detachment basin that is well mapped where the basin has been inverted by young uplift, and is inferred to be present beneath deep modern basins in the western Salton Trough and Coachella Valley where inversion has not occurred (Axen and Fletcher, 1998;Janecke et al, 2010). Regional extension and lithospheric rupture across the plate boundary have continued to the present day, resulting in rapid subsidence and accumulation of Colorado River-derived sediment in basins as much as 10-12 km deep (Fuis et al, 1984;Elders and Sass, 1988;Herzig et al, 1988;Schmitt and Vazquez, 2006;Schmitt and Hulen, 2008;Dorsey, 2010).…”
Section: Geologic and Tectonic Settingmentioning
confidence: 99%
“…The geothermal system is situated within sedimentary Pliocene-Pleistocene rocks that were deposited in the continental basin of the Salton Trough [3] and is well characterized, both geologically and geophysically [4]. Studies of radionuclide behavior in the SSGF [1,2] have shown that radium and lead isotopes are present in high concentrations due to the formation of complexes with Cl-, the high salinity of the brines, and the low abundance of available adsorption sites.…”
Section: Introductionmentioning
confidence: 99%